Green synthesis of Lawsonia inermis-mediated zinc ferrite nanoparticles for magnetic studies and anticancer activity against breast cancer (MCF-7) cell lines - Sarala, E.; Madhukara Naik, M.; Vinuth, M.; Rami Reddy, Y. V.; Sujatha, H. R. (Journal of materials science. Materials in electronics, 2020)
Magnetic spinel zinc ferrite nanoparticles have been prepared via simple, green, cost effective and eco-friendly methods. The development of a single cubic phase of prepared zinc ferrite is affirmed by XRD with an average crystallite size of 17.12 nm. FTIR analysis confirms the modes of the cubic ZnFe 2 O 4 phase due to the stretching and bending vibrations of Zn–O (tetrahedral site) and Fe–O (octahedral site) bonds. FESEM micrographs revealed the formation of homogeneous and agglomerated ZnFe 2 O 4 nanoparticles. EDAX spectrum shows the elemental composition of the synthesized zinc ferrite nanoparticles. Investigation of magnetic properties viz remanent magnetization, saturation magnetization and coercivity were found to be 37.0 emu/g, 42.9 emu/g and 11.9 Oe, respectively. The magnetic properties confirmed by the vibrating sample magnetometer exhibit ferromagnetic behaviour of synthesized zinc ferrite nanoparticles. Furthermore, synthesized zinc ferrite nanoparticles showed good anticancer activity against breast cancer (MCF-7) cell lines.